Recursos do FPM e FUNDEB: impacto no desempenho escolar nos municípios cearenses nos triênio 2007, 2009 E 2011 - Lins, Francisco Gennison Sales (2014)
Considedering the importance of contribution of funds received by the 184 municipalities of Ceará stote through FUNDEB and FPM, this study investigated the impact of these transfers on the IDEB index of two groups for analysis, the first to the 4th/5th year and the second of the 8th/9th year in years for 2007, 2009 and 2011. The database used is composed of the variables that represent the IDEB index for the 4th/5th year, 8th/9th year and an average between these two indices and the logarithm of FPM and FUNDEB variables. The first variables were extracted from the website of the National Institute for Educational Studies Teixeira - INEP for public schools in the municipalities of Ceará. The data of the FUNDEB and FPM were extracted from the electronic site of the Nacional Treasury - STN for the years 2007, 2009 and 2011. The descriptive analysis showed an increasing trend in the index IDEB accompanied by an increasing trend in the transfer of FUNDEB, which has not been accompanied by FPM. With this evidence, the estimations made, using Panel Data for fixed and random effects, resulted in positive and significant effects of the transfer of FUNDEB on the IDEB index for all groups.